2016
DOI: 10.1155/2016/8182071
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Treatment of Lateral Elbow Pain: A Nonrandomized Pilot Study

Abstract: In planning for a large-scale multicenter trial to evaluate the effect of acupuncture for the treatment of lateral elbow pain, a pilot study was conducted. This was a prospective, investigator- and patient-blinded, nonrandomized, placebo controlled trial. Subjects were evaluated at baseline, before fourth, seventh, and ninth treatment, and at a two-week posttreatment follow-up. The treatment group received unilateral acupuncture at LI 10 and LI 11 at the affected side with manual needle manipulation; the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Clinical practice suggests that acupoint specificity plays an important role in guiding clinical treatment [ 7 , 8 , 38 ]. Using the improved rabbit acute bradycardia model, a suitable animal model for the human bradycardia disease [ 26 ], we found that stimulating PC6 (the pericardium meridian, a clinical indicator of angina [ 39 , 40 ], arrhythmia [ 41 ], and gastritis [ 42 ]) with EA induced a significant increase in heart rate during bradycardia induced by acute myocardial ischemia in rabbits, and the recovery of relative heart rate was significantly higher than that in the LU7 (the lung meridian, a clinical indicator of cough [ 43 ] and headache [ 44 ]) and LI11 (the large intestine meridian, a clinical indicator of arm pain [ 45 ] and hypertension [ 46 ]) groups (Figures 4 and 5 ). This indicates that the effect of acupuncture cannot be obtained by applying EA stimulation on any random point on the body.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical practice suggests that acupoint specificity plays an important role in guiding clinical treatment [ 7 , 8 , 38 ]. Using the improved rabbit acute bradycardia model, a suitable animal model for the human bradycardia disease [ 26 ], we found that stimulating PC6 (the pericardium meridian, a clinical indicator of angina [ 39 , 40 ], arrhythmia [ 41 ], and gastritis [ 42 ]) with EA induced a significant increase in heart rate during bradycardia induced by acute myocardial ischemia in rabbits, and the recovery of relative heart rate was significantly higher than that in the LU7 (the lung meridian, a clinical indicator of cough [ 43 ] and headache [ 44 ]) and LI11 (the large intestine meridian, a clinical indicator of arm pain [ 45 ] and hypertension [ 46 ]) groups (Figures 4 and 5 ). This indicates that the effect of acupuncture cannot be obtained by applying EA stimulation on any random point on the body.…”
Section: Discussionmentioning
confidence: 99%
“…One of the research partners from the Changchun University of Chinese Medicine (WFC) had had extensive experience in treating lateral elbow pain and suggested a simple acupuncture technique consisting of two local acupoints (Large Intestine 10 and Large Intestine 11) and a specific needle technique (Wagging the Dragon's Tail). The research partners decided that a pilot study would be necessary to ensure that the technique was efficient and asked the Chinese research group to conduct a pilot study before incorporating the acupuncture technique [7]. …”
Section: Discussionmentioning
confidence: 99%
“…However, there is inconclusive evidence that needle acupuncture has a specific action in the treatment of this debilitating condition as shown by Gadau et al in the latest systematic review on the topic due to low methodological quality and the small sample sizes of the individual studies [6]. The result from a nonrandomised controlled pilot study ( n = 40) from our group suggests that acupuncture may be helpful in improving function and pain associated with LEP [7]. In this study, the treatment group ( n = 20) received nine unilateral acupuncture treatments at LI 10 and LI 11 on the affected side with manual needle manipulation while the control group ( n = 20) received nine sham-laser-acupuncture at the same acupoints.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations